Thermomechanical analysis of polymeric foams subjected to cyclic loading: Anelasticity, self-heating and strain-induced crystallization. (22nd September 2017) - Lachhab, A.; Robin, E.; Le Cam, J.-B.; Mortier, F.; Tirel, Y.; Canevet, F.
Abstract: The present study investigates the thermomechanical behavior of TPU foams. Different densities were tested, including the compact state, which ensures a relevant characterization of the relative effect of the void volume fraction. A series of cyclic uniaxial tensile tests was carried out at different loading rates and different specimen densities. The effects of the density and the loading conditions on the softening, the residual strain and the hysteresis have been characterized. The thermal responses exhibit numerous particularities. First, a threshold effect in terms of the density on the self-heating has been highlighted. Second, entropic effects are weighted by energetic effects (internal energy variations) during the deformation. Typical changes in the thermal response highlight that strain-induced crystallization (SIC) and crystallite melting occur during the deformation. The characteristic stretches of this phenomenon evolve with the maximum stretch applied, which increases the residual stretch, and the number of cycles, which induces the softening. Decreasing the density decreases the crystallinity: the volume of crystallizing matter is lower and cell wholes become more and more thin, which decreases the mobility of the molecular chains. These effects cannot be predicted from the mechanical responses and the present study provides therefore information of importance to better understand and model the effects of the density and the loading conditions on the thermomechanical behavior of TPU foams. Graphical abstract: Highlights: Thermomechanical response of TPU foams has been fully characterized. Different densities were tested, including the compact state. A threshold effect in terms of the density on the self-heating has been highlighted. Typical changes in the thermal response are due to SIC and crystallite melting. Decreasing the density decreases the crystallinity.